2020
DOI: 10.1002/2211-5463.13036
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal immunolocalisation of REST in the brain of healthy ageing and Alzheimer’s disease rats

Abstract: In the brain, REST (Repressor Element-1 Silencing Transcription factor) is a key regulator of neuron cell-specific gene expression. Nuclear translocation of neuronal REST has been shown to be neuroprotective in a healthy ageing context. In contrast, inability to upregulate nuclear REST is thought to leave ageing neurons vulnerable to neurodegenerative stimuli, such as Alzheimer's disease (AD) pathology. Hippocampal and cortical neurons are known to be particularly susceptible to AD-associated neurodegeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Other studies have shown an increased cytoskeleton hypertrophy or increased complexity of astrocytes near Aß plaques using GFAP immunolabeling in the hippocampus of 6, 12, and 18-month-old TgF344 male and female rats [Swedish mutation in APP and humanized PSEN1 (Cohen et al, 2013)] (Mampay et al, 2020), in the dentate gyrus and hippocampus CA1 of 18-month-old 3xTg male mice (Olabarria et al, 2010) and in the cerebral cortex of 3, 6 and 12-month-old APP-PS1 mice (increase in volume and process length) (Li et al, 2020). A sex-specific increase in the abundance of hypertrophic astrocytes in 7-9 month-old APP-PS1 female compared to male mice was observed in the outer molecular layer of the dentate gyrus (Richetin et al, 2017).…”
Section: Morphological and Ultrastructural Heterogeneity Of Astrocytesmentioning
confidence: 99%
“…Other studies have shown an increased cytoskeleton hypertrophy or increased complexity of astrocytes near Aß plaques using GFAP immunolabeling in the hippocampus of 6, 12, and 18-month-old TgF344 male and female rats [Swedish mutation in APP and humanized PSEN1 (Cohen et al, 2013)] (Mampay et al, 2020), in the dentate gyrus and hippocampus CA1 of 18-month-old 3xTg male mice (Olabarria et al, 2010) and in the cerebral cortex of 3, 6 and 12-month-old APP-PS1 mice (increase in volume and process length) (Li et al, 2020). A sex-specific increase in the abundance of hypertrophic astrocytes in 7-9 month-old APP-PS1 female compared to male mice was observed in the outer molecular layer of the dentate gyrus (Richetin et al, 2017).…”
Section: Morphological and Ultrastructural Heterogeneity Of Astrocytesmentioning
confidence: 99%